Acacia angustissima: Its anti-nutrients constituents, toxicity and possible mechanisms to alleviate the toxicity - a short review - Odenyo, A.A.; Osuji, P.O.; Reed, J.D.; Smith, A.H.; Mackie, R.I.; McSweeney, C.S.; Hanson, Jean (Springer, 2003)
In most tropical countries poor nutrition limits ruminant productivity. The main feed resources include native pasture and crop residues, which are low in nitrogen (6.2-10.6 g/kg DM) and high in fibre (676-772 g/kg DM). Nutritional deficiencies of these feeds can be alleviated by supplementation with fodder trees such as Acacia angustissima, which are multipurpose, have outstanding agronomical attributes and are rich in nitrogen (33.2-40.8 g/kg DM). However, feeding A. angustissima without adaptation caused toxicity to sheeRats fed diets containing 20% A. angustissima died within 2-5 d. Intake and average daily gain (6.0 and 0.5 g/d) were significantly (P< 0.05) reduced in rats fed a diet containing 70% acetone extract compared to the rats fed the control diet (8.8 and 3.1 g/d). Addition of polyethylene glycol (PEG) improved in-vitro gas and ammonia production from A. angustissima leaves (gas, 3.9 to 13.4 ml/100g DM; ammonia, 2.8 to 8.5 mM). PEG also increased DM intake (696 and 860 g /d) in sheep fed A. angustissima. These results suggested that tannin contributed to the negative effects of A. angustissima. Non-protein amino acids (4-N-acetyl-2, 4-diaminobutanoic acid, acetyl diaminopropionic acid, oxalyl diamino butyric, oxalyl diaminopropionic) have also been isolated from A. angustissima leaves. Feeding A. angustissima to sheep by gradually increasing levels in the diet prevented toxicity. Additionally, transfer of rumen contents from adapted to non-adapted sheep prevented toxicity of A. angustissima. These observations suggested that adaptation was at the microbial level. Current work to alleviate the toxicity of A. angustissima is therefore focused on microbial adaptation and detoxification. Tannin-tolerant bacteria have been isolated from sheep adapted to A. angustissima and free-ranging animals. Work on non-protein amino acids is underway. Overcoming the negative effects of the anti-nutritional factors in A. angustissima would not only improve livestock productivity but also result in improvement of the environment.